The Influence of 15-Second TikTok Videos and Organic Testimonials on Environmental Awareness and Purchase Intention of Sustainable Fashion in Bandung - Kristian Panjaitan, Feliks Anggia Binsar; Arini, Rani Eka; Bunyamin, Ilham Akbar (Westscience Press, 2025)
This study examines the influence of 15-second TikTok videos and organic testimonials on environmental awareness and purchase intention in the context of sustainable fashion in Bandung. Using a quantitative approach, data were collected from 170 respondents and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that both TikTok videos and organic testimonials significantly impact environmental awareness and purchase intention, with organic testimonials demonstrating a stronger effect. Environmental awareness is identified as a key precursor to purchase intention, emphasizing the importance of educational and marketing efforts to promote sustainability. The findings provide actionable insights for sustainable fashion brands to leverage social media and peer-generated content in shaping consumer behavior and supporting environmental objectives.